EVALUATING THE VALUE OF REAL ESTATE AFTER NATURAL DISASTER (CASE STUDY OF CITRALAND MANADO) - Palit, Wulan Pricillia; Worang, Frederik G. (Jurnal EMBA : Jurnal Riset Ekonomi, Manajemen, Bisnis dan Akuntansi, 2018)
Abstract: Changes in the values of real estate could have unpredictable consequences. Many factors enter real estate market and affect the market price, one of the price-setting factor also flood risk zone (FRZ) to which more attention is paid in relation to the market value. Natural disaster is the occurrence of an extreme hazardous event that impacts on Citraland real estate causing damage, disruption and leaving the affected communities unable to function normally without outside assistance. The main purpose of this research is to evaluate the value according to consumer perception of the houses in Citraland Manado. This research uses qualitative research with an exploratory approach through in-depth interviews. By using purposive sampling eight informants has been selected in order to collect the data. Based on the results there are several factors that influencing the value of Citraland Manado before and after natural disaster, most influenting factor are the brand and facilities and there are also several factors like security, environment and also location that influencing the value of Citraland but also maintain the value after natural disaster hit Citraland Manado in 2014. And the effect of natural disaster to the value of real estate is just temporary.Keywords: value, natural disaster, real estate